The economic burden of coronary heart disease in the UK. Issue 6 (1st December 2002) - Liu, J L Y; Maniadakis, N; Gray, A; Rayner, M
Abstract : Objective: To estimate the economic burden of coronary heart disease in the UK using both direct and indirect costs. Design and setting: A prevalence based approach was used to assess coronary heart disease related costs from the societal perspective. Patients: All UK residents in 1999 with coronary heart disease (ICD 9 codes 410–414 and ICD10 codes I20–I25). Main outcome measures: Direct health care costs were estimated from spending on prevention, accident and emergency care, hospital care, rehabilitation, and drug treatment. Direct non-health service costs were estimated from data on informal care. "Friction period" adjusted productivity costs were estimated using the human capital approach from lost earnings attributable to coronary heart disease related mortality and morbidity. The friction period is the period of employees' absence from work before the employer replaces them with other workers. Failure to adjust for this factor would overstate production loss. Results: Coronary heart disease cost £1.73 billion to the UK health care system in 1999: £2.42 billion in informal care and £2.91 billion in friction period adjusted productivity loss; 24.1% of production losses were attributable to mortality and 75.9% to morbidity. The total annual cost of all coronary heart disease related burdens was £7.06 billion, the highest of all diseases in the UK for which comparable analyses have been done. Conclusions: Coronary heart disease is a leading public health problem in the UK in terms of the economic burden from disease. Cost estimates would be substantially understated if informal care/productivity costs were excluded.